IPTEK BAGI MASYARAKAT (IBM) PELAKU USAHA BAWANG MERAH GORENG DI JATIREJO NGANJUK - Cahyaningrum, Sari Edi; Heryastuti, Nuniek; Hidajati, Nurul (Universitas Negeri Surabaya, 2019)
Intention of activity of this Pengabdian pada Masyarakat (PKM) is to conduct activity of training and is adjacent of partner Industri Kecil Menengah (IKM) in developing the effort shallot fry. Partner during the time have run the effort shallot fry traditionally, yielded to be product to be sold to whole sale. Special goals to be got by partner are skilled way of making shallot fry which with quality evaluated from health side and competent sell. Owning knowledge and earn system applied of management marketing and its business activity, owning good packaging and also have permission legality of is effort. Efektivity and of optimalization of program through giving of training and adjacent in making of shallot fry, giving training of managemen of marketing, assisting to make packaging desain and manage permission legality is effort. Results of this activity indicate that partner very enthusiastic followed of training phase and is adjacent effort which is conducted. Partner feel to like because its effort permission of its fair to middling quality of goodness, its legality also have fufilled big sebagain so that partner feel balmy to run the effort. Ability to produce shallot fry to be expected increasing so that will push society create employment and improving economics and production.